Desenvolvimento de sistema de rastreamento solar gravitacional e pendular para painel fotovoltaico isolado - Wissmann, Jorge Augusto (2024)
The contribution for photovoltaic energy is constantly growing within the energy matrix of each country. Within this renewable energy system there is a constant optimization, which can appear in several ways: in the advancement of photovoltaic cell technologies, in the impedance adjustment, in the inverter, in the storage of the collected energy (on-grid or off-grid), in cooling the cells, cleaning the modules, adopting bifacial photovoltaic system and, as the subject of this paper, the tracking of the solar position. A review of the types, techniques and classifications of the most varied solar trackers is presented through bibliographic research in recent international journals. Quantitative and qualitative surveys are exemplified, demonstrating in which situations they become feasible. A prototype tracker structure was idealized and here produced, classified within this review as being a chronological by its fixed rate of rotation, and manual because need recharges, with single potential mechanical azimuthal axis, not motorized, and analogic (without sensors or algorithms). Details of its principles, production and work are described in this paper. The prototype created was compared to another stationary panel and showed an increase of 9.69% in average energy generation during the two-month period of this research, statistically significant difference, as well as an improvement in collection efficiency in the first hours and at the end of days. The temperature of the panel equipped with the tracking prototype showed higher values at the beginning and end of each day